Nivel de ventas de la empresa Cyber Act De La Ciudad De Babahoyo. - Inga Mayorga, Genesis Lisbeth (2022)
The present case study was carried out in the CYBER ACT Company of the city of Babahoyo, with the objective of analyzing the level of sales that the company maintains and that affect the development of its activities, having found different problems that affect each one. Of the tasks performed by the entity's workers with respect to the service they offer to customers, as a first point, different contextualizations were explored that allowed a precise understanding of the theme of this study. The methodology used in this case was the deductive and inductive method given that through the analysis of the information collected, the sales process of the organization was revealed, as well as the bibliographic method that allowed locating and accessing authors' theories. After the methodology, information collection tools were used such as: the survey and statistical analysis directed at the company's clients, this tool allowed to focus on the body language that each client, their behavior, including visual elements that they showed at the time of fill out the survey, another of the information collection instruments was: the observation sheet, with the aim of observing compliance with the execution of activities. In addition to all the data obtained, it was deduced that the company CYBER ACT does not have commercial objectives with defined goals that allow it to increase the demands for its services, as well as maintain a low level of training for its employees that have not allowed it to these establish a service that meets the needs of users.